Sovereign Debt: Forgiving and Forgetting Reconsidered - Wolfgang Pesendorfer (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
In this note we show that even if after default a sovereign can make deposits on a Swiss bank account, the exclusion from future debt is sufficient to deter a patient country from default. In contrast to the work by Bulow and Rogoff (1989) we assume that there is a fixed set of standard assets on the world financial markets in which the country can trade. In this setting the exclusion from future borrowing may seriously limit a country's ability to smooth consumption. Therefore the traditional reputational logic can be applied.
Keywords: 330